2SB-10 DRYER INTERIOR TEMPERATURE, SENSOR THROUGH MODERATION WITH THE HELP IMPROVEMENT (Journal of Science-Innovative Research in Uzbekistan, 2024)
2SB-10 drying drum is widely used in cotton ginning enterprises. During the drying process, a temperature sensor is placed on the drum in order to prevent raw materials from burning due to high temperature. As a result, regular control of the temperature inside the drum is achieved. 2SB-10 drying drum is improved and the process is automated.